2009
DOI: 10.1111/j.1751-7117.2009.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of B‐type Natriuretic Peptide, New York Heart Association Classification and Depression on Quality of Life in Nonhospitalized Heart Failure Patients

Abstract: Healthcare providers should be concerned with improving the quality of life (QOL) of patients with heart failure (HF) because disease-specific QOL is linked to disease progression. The present study investigated the significance of elevated b-type natriuretic peptide (BNP), NYHA classification and depression to HF-related QOL to develop better management strategies. Outpatient subjects with left ventricular systolic dysfunction (n=108; mean age=64.9+/-12) completed the self-administered Minnesota Living with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 47 publications
(108 reference statements)
0
15
1
Order By: Relevance
“…Their results showed a mean for each item that ranged from 1.8 to 2.8, indicating that the clinical manifestations of heart disease had an impact on quality of life. 26 In a US study, the mean of the total score for quality of life was 48, 30 which was higher than the mean of 23 found in the present study. This indicates that the patients in our study experienced a lower impact from their disease on their quality of life.…”
Section: Discussioncontrasting
confidence: 74%
“…Their results showed a mean for each item that ranged from 1.8 to 2.8, indicating that the clinical manifestations of heart disease had an impact on quality of life. 26 In a US study, the mean of the total score for quality of life was 48, 30 which was higher than the mean of 23 found in the present study. This indicates that the patients in our study experienced a lower impact from their disease on their quality of life.…”
Section: Discussioncontrasting
confidence: 74%
“…Other researchers examining the relationship between depressive symptoms and HRQOL in patients with HF in cross-sectional studies have identified depressive symptoms as an independent predictor of HRQOL. 2,710 Similar to our study, these investigators measured HRQOL using HF-specific measures—either the Minnesota Living with HF questionnaire or the Kansas City Cardiomyopathy questionnaire. In one cross-sectional study, Faller et al 32 evaluated depressive symptoms, NYHA functional status, and HRQOL in outpatients with HF.…”
Section: Discussionmentioning
confidence: 87%
“…2 This hypothesis is based on results from multiple cross-sectional studies showing that depressive symptoms measured at baseline independently predict baseline HRQOL in patients with HF. 2,710 Although few investigators have examined the natural trajectory of depressive symptoms in patients with HF, 1114 the severity of depressive symptoms may vary over time. It is not known whether a positive or negative change in depressive symptoms over time leads to a parallel change in HRQOL.…”
Section: Introductionmentioning
confidence: 99%
“…The FEW16 should be used on a larger and—regarding NYHA class—more heterogeneous sample to generate conclusive findings. The significant correlation of major depression with all FEW16 scores reflects the negative impact of depressed mood on the physical and psychological dimension of QoL in HF patients found earlier . Age and sex did not significantly correlate with any FEW16 score.…”
Section: Discussionmentioning
confidence: 62%